PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BANK PERKREDITAN RAKYAT - JELI NATA LIYAS; REZA PRIMADI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. Nowadays the banking industry is entering a period where competition has become very competitive. Competition is such a great challenge for every company. Hence a strong work discipline is required from every employee in order to survive and win the competition The main objective of this research is to thoroughly determine The Influence of Work Discipline on Employee Performance at BPR Rokan Hulu. The sampling technique used is census method where the whole population is taken into account in which in this research amounted to 41 respondent. The recapitulation result of respondents answer on Work Discipline (X) get average value 3.64 and Results Summary of Answers the respondents about Employees Performance (Y) get average value 3.79 . This result indicates that the criteria of respondents answer is agreed. Based on the research result, Work Discipline influences significant of the Performance of Employees. It shows the significant influence of Work Discipline on Employee Performance. This refers to t count > t table which is 10.770 > 2.023, then H1 is accepted. This is proven by testing the Coefficient of Determination (R2) with a yield equal to 74.8%.